Dismantling or Perpetuating Gender Stereotypes. – The Case of Trans Rights in the European Court of Human Rights’ Jurisprudence - Hansen, Caroline (The Age of Human Rights Journal, 2022)
The European Court of Human Rights (the Court) considers gender identity “a fundamental aspect of the right to respect for private life” (AP, Garçon & Nicot v France, 2017), and has taken important steps towards ensuring that this right is implemented in Council of Europe states. The Court has thus held that trans persons cannot be required to undergo “sterilisation surgery or treatment” to have their gender legally recognised by the State (AP, Garçon & Nicot v France). However, where such advancements have opened doors for many trans people to access legal gender recognition without undergoing unwanted or impossible surgeries, certain requirements remain. Where the gender identity of trans persons must be ‘verified’ by a third-party to enable legal gender recognition, this bears the risk of seeing stereotypical visions of gender enforced, devaluing the general aim of dismantling gender stereotypes for all. This paper will analyse gender stereotypes appearing in cases of the Court relating to trans persons, and explore alternatives to the current systems of legal gender recognition, which may aid in dismantling gender stereotypes for persons of all gender identities.